Subnational Foreign Policy in a Global Context: The Case of Córdoba’s Paradiplomacy toward the United States and China (2011–2023) - Trebucq, Federico (Journal of Paradiplomacy and City Networks, 2025)
This study analyzed the paradiplomatic activity of the Córdoba provincial government toward the United States and China from 2011 to 2023, aiming to identify similarities and differences in the strategies adopted in relation to both global powers, while considering possible constraints arising from the international context. The research is framed within the field of paradiplomacy studies, conceiving of non-central governments as actors with autonomous capacity for engagement in transnational settings. A mixed-method approach was employed: a qualitative analysis that contextualized the actions according to their type, institutional framework, and thematic dimensions; and a quantitative analysis that classified the 98 identified actions based on the role of the provincial government (as actor or facilitator) and the scope of application (domestic or international). The findings disclosed that Córdoba’s international engagement was predominantly economic and commercial, with a facilitator–international profile, and that while relations with the United States focused on services, technology, and education, those with China emphasized infrastructure, agro-industry, and investment, in both cases without evidence of a long-term strategic plan.